Docosahexaenoic acid inhibits TNFα-induced ICAM-1 expression by activating PPARα and autophagy in human endothelial cells. (December 2019) - Lin, Hung-Chih; Lii, Chong-Kuei; Lin, Ai-Hsuan; Li, Chien-Chun; Tsai, Chia-Han; Pan, Shiuan-Kai; Yang, Ya-Chen; Huang, Chin-Shiu; Reshi, Latif; Chen, Haw-Wen
Abstract: Inflammation plays a key role in the development of cardiovascular disease (CVD), and docosahexaenoic acid (DHA) is recognized to fight against CVD. PPARα belongs to the nuclear hormone receptor superfamily and can interfere with inflammatory processes. Autophagy can degrade inflammasome proteins and counteract inflammation. Overexpression of intercellular adhesion molecule (ICAM) 1 in endothelial cells contributes to monocyte migration into the vascular intima. Here we investigated the mechanisms by which DHA inhibits TNFα-induced ICAM-1 expression in EA. hy926 endothelial cells. DHA markedly activated PPARα and suppressed TNFα-induced ICAM-1 expression, ICAM-1 promoter activity, p65 nuclear translocation, NFκB and DNA binding activity, and THP-1 cell adhesion. PPARα knockdown abolished the ability of DHA to inhibit TNFα-induced ICAM-1 expression and THP-1 cell adhesion. The PPARα antagonist GW6471 reversed the inhibitory effect of DHA on TNFα-induced ICAM-1 expression, p65 nuclear translocation, NFκB and DNA binding activity, and THP-1 cell adhesion. DHA significantly activated autophagy as evidenced by the formation of autophagosomes and increased LC3II protein expression. By contrast, wortmannin, which inhibits autophagy, abrogated DHA-induced autophagy and the inhibition of TNFα-induced ICAM-1 protein expression by DHA. Our results suggest that DHA likely inhibits TNFα-induced ICAM-1 expression by activating PPARα and autophagy. Graphical abstract: Image 1 Highlights: The anti-inflammatory activity of DHA in the vascular endothelium partially contributes to its cardioprotective effect. DHA activates PPARα and suppressed TNFα-induced ICAM-1 expression, p65 nuclear translocation,  and THP-1 cell adhesion. DHA significantly activates autophagy as evidenced by the formation of autophagosomes and increased LC3II protein expression.